Antioxidant pectins from eggplant (Solanum melongena) fruit exocarp, calyx and flesh isolated through high-power ultrasound and sodium carbonate - Higuera Coelho, Ricardo Alejandro (2023)
Dried and milled eggplant fruit peel and calyces (PC) and mesocarp, placenta and core (Mes) were utilized as natural sources of valuable chemicals. Pectins were extracted with 0.1 M Na2CO3 (1 h; 23 °C). A high-power ultrasound (US) pretreatment (10 min net time; 12.76 W/cm2 power intensity) in 10:200 (g/mL) powder:water ratio led to the lowest solvent and energy consumptions after the subsequent 0.1 M Na2CO3 stirring, permitting the highest recoveries of uronic acid (UA) from PC and Mes (80.25 and 93.8 %, respectively). Homogalacturonans (>65 % w/w UA) of low degree of methylesterification, of acetylation, and 90,214–138,184 Da molecular weights with low polydispersity (≈1.32–1.40) were obtained. They included released ferulate (≈3.5 mg/100 g) esterified pectins. Antioxidants (caffeoylquinic acid, putrescine and spermidine derivatives, β-carotene, lutein) gave additional technological value to their thickening effect as pectins protected tryptophan, tyrosine, alkyl side chains and sulfhydryl of skim milk proteins from UV-C photo-oxidation. //Resumen: La cáscara y los cálices (PC) y el mesocarpio, la placenta y el núcleo (Mes) de berenjena seca y molida se utilizaron como fuentes naturales de productos químicos valiosos. Las pectinas se extrajeron con Na2CO3 0,1 M (1 h; 23 °C). Un pretratamiento con ultrasonido (US) de alta potencia (10 min de tiempo neto; intensidad de potencia de 12,76 W/cm2) en una proporción de polvo:agua de 10:200 (g/mL) condujo a los consumos de energía y disolvente más bajos después de la agitación posterior con Na2CO3 0,1 M , permitiendo las mayores recuperaciones de ácido urónico (AU) de PC y Mes (80,25 y 93,8 %, respectivamente). Se obtuvieron homogalacturonanos (>65 % p/p UA) de bajo grado de metilesterificación, de acetilación y pesos moleculares 90,214–138,184 Da con baja polidispersidad (≈1.32–1.40). Incluyeron pectinas esterificadas feruladas liberadas (≈3,5 mg/100 g). Los antioxidantes (ácido cafeoilquínico, derivados de putrescina y espermidina, β-caroteno, luteína) dieron un valor tecnológico adicional a su efecto espesante ya que las pectinas protegieron el triptófano, la tirosina, las cadenas laterales de alquilo y el sulfhidrilo de las proteínas de la leche descremada de la fotooxidación UV-C.